Understanding Teacher Candidate Misconceptions and Concerns about Differentiated Instruction. Issue 1 (2nd January 2019) - Dack, Hilary
Abstract: While teacher education programs are expected to teach effective methods of differentiating instruction, limited research to date has examined the meaning-making processes through which candidates build an understanding of this complex philosophy of teaching and learning. Drawing upon activity theory, this interpretive qualitative study examined how candidates' understandings of differentiation's conceptual and practical tools—and their concerns about its implementation–changed as they encountered accurate, in-depth information about the model in a course on differentiation. Data sources included interviews, assignments, and observations. Findings suggested candidates entered the course with common misconceptions about differentiation's conceptual tools. Although many candidates originally conceptualized differentiation as a set of practical tools, they later viewed it as a conceptual framework that guides practice. As candidates appropriated practical tools of differentiation, common concerns about implementing differentiation diminished. Implications include questions teacher educators who teach candidates about differentiation should pose to guide their own instruction.